Data on the migration of health-care workers: sources, uses, and challenges - Khassoum Diallo (The World Health Organization, 2004)
The migration of health workers within and between countries is a growing concern worldwide because of its impact on health systems in developing and developed countries alike. Policy decisions need to be made at the national, regional and international levels to manage more effectively this phenomenon, but those decisions will be effective and correctly implemented and evaluated only if they are based on adequate statistical data. Most statistics on the migration of health-care workers are neither complete nor fully comparable, and they are often underused, limited (because they often give only a broad description of the phenomena) and not as timely as required. There is also a conflict between the wide range of potential sources of data and the poor statistical evidence on the migration of health personnel. There are two major problems facing researchers who wish to provide evidence on this migration: the problems commonly faced when studying migration in general, such as definitional and comparability problems of "worker migrations" and those related to the specific movements of the health workforce. This paper presents information on the uses of statistics and those who use them, the strengths and limitations of the main data sources, and other challenges that need to be met to obtain good evidence on the migration of health workers. This paper also proposes methods to improve the collection, analysis, sharing, and use of statistics on the migration of health workers.